Characterization of Gross Domestic Expenditure on R&D in Latin American countries during 2008-2017 (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Gross domestic expenditure on R&D is one of the most analyzed indicators in terms of growth and economic development of a country. Improving this indicator would lead to the achievement of the SDG that UN Member States adopted in 2015, which responds to build resilient infrastructure, promote inclusive and sustainable industrialization, and foster innovation. In this research, a descriptive analysis of the GDE on R&D indicator of Latin American countries, in the period 2008 - 2017, has been carried out in order to analyze and compare it. Firstly, information is presented on the GDE on R&D indicator. Then, the analysis and comparison of the indicator among Latin American countries is shown. In the same way, for the countries that obtain better results, they are compared with the values of the indicator of other countries of Ibero-America and North America. Brazil is the only Latin American country that presents the highest average value of the indicator (0.012), above the average value of Latin American and Caribbean countries, and even of Ibero-American countries.